Social Media Efficacy on Athletes’ Training and Workout During Covid-19 Pandemic in Kwara State, Nigeria - Elijah Kayode , Falaye; Tunrayo Ajadi, Memunat; Yinusa Owolabi, Abdulraheem (Universitas Ahmad Dahlan, 2023)
Background: It will be interesting to say that the rise in e-sports participation and online training is more prevalence than before due to COVID-19 pandemic. It is in view of this that the study investigated social media efficacy on athletes training and workout during COVID-19 pandemic in Kwara State, Nigeria. The objectives of this study were to assess. influence of use of YouTube on athlete training and workout, ii. influence of facebook and twitter on athlete training and workout during COVID-19 pandemic. Contribution: Coaches and athletes are encouraged to embraced digitilization of sports as a mean of effective communication. Method: Descriptive research design of the survey type was used. The population of the study comprises all coaches and athletes in the study area. The Multistage sampling procedures of stratified, purposive and random sampling techniques were used to select 85 respondents. A researcher-structured questionnaire was used for the study. The instrument was validated and tested for reliability using the Pearson Product Moment Correlation (PPMC). A correlation co-efficient of 0.65r was obtained. The data collected were analysed using inferential statistics of chi-square (x2) to test the formulated hypotheses set for the study at 0.05 alpha level. Results: The Results revealed that the use of YouTube, facebook, twitter and use of video calls through Skype had significant influences on athletes training and workout during COVID-19 pandemic. Conclusion: The study concluded that use of YouTube, facebook, twitter and virtual platform were fundamental and significant to athletes training and workout during Covid-19 pandemic lockdown